Evaluation of Publication Rate of Forensic Medicine Specialty Theses in Turkey - Çağlayan, Derya; Çelik, Cemil; Kaya, Ahsen; Aktaş, Ekin Özgür (The Bulletin of Legal Medicine, 2020)
Objective: The aim of this study is to investigate the publication rate of Forensic Medicine specialty theses in national and international journals.Materials and Methods: The Thesis Center database of Council on Higher Education was searched for medical specialty theses written between 1983-2016. Another screening was done using the resident and mentor names as well as thesis title on Ulakbim, Türk Medline, Google Scholar, Web of Science, PubMed databases. The years in which the theses were done and the articles were published, database of the journal, resident’s order among the authors, type of research, thesis subjects were recorded. Results: It was found that 77 (32.6%) out of a total of 236 theses written between 1983-2016 were published. Fifteen-point two percent of these theses were published in Science Citation Index-Expanded/Social Sciences Citation Index, 11.9% were published in international, and 5.5% in national indexed journals. The mean publication time was 2.95±2.49 years. It was also found that the resident was the first author in 85.7% of the articles, and 53.2% of the published theses were prospective studies. Most frequently article subjects were in the fields of Forensic Pathology (26%) and Forensic Psychiatry (23.4%).Conclusion: Publishing rate of theses in Forensic Medicine was similar to the data regarding publication rates of theses in different medical specialty fields in our country and abroad; however, it is below the level desired. It is of utmost importance to generate solutions to facilitate the process including but not limited to mentors that are encouraging and instructive,...
Keywords: forensic medicine; publication; specialty; these